2019
DOI: 10.1021/acsnano.9b05974
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Coordination Polymer Based Nanovaccine for Tumor Immunotherapy

Abstract: Tumor vaccines to induce robust immunity for cancer treatment have attracted tremendous interests in cancer immunotherapy. In this work, a type of cancer vaccine is prepared by using nanoscale coordination polymer (NCP) formed between Mn 2+ ions and a nucleotide oligomerization binding domain 1 (Nod1) agonist, meso-2,6diaminopimelic acid (DAP), as the organic ligand, to encapsulate a model protein antigen, ovalbumin (OVA). The obtained OVA@Mn-DAP nanoparticles could act as an effective tumor vaccine to promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 42 publications
1
67
0
Order By: Relevance
“…Therefore, it is highly desirable to improve the immune response rate and selectively destroy primary solid tumors and metastatic lesions. In recent years, immunotherapy combined with nanotechnology, defined as nanoimmunotherapy, has shown promising performance for cancer therapy [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. Among these therapeutics, metal-organic frameworks (MOFs), as a crystal material, has been widely studied in biomedical field [ [31] , [32] , [33] , [34] , [35] , [36] , [37] ].…”
Section: Introductionsmentioning
confidence: 99%
“…Therefore, it is highly desirable to improve the immune response rate and selectively destroy primary solid tumors and metastatic lesions. In recent years, immunotherapy combined with nanotechnology, defined as nanoimmunotherapy, has shown promising performance for cancer therapy [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. Among these therapeutics, metal-organic frameworks (MOFs), as a crystal material, has been widely studied in biomedical field [ [31] , [32] , [33] , [34] , [35] , [36] , [37] ].…”
Section: Introductionsmentioning
confidence: 99%
“…Fluorescence imaging and magnetic resonance (MR) can be used to observe that OVA@Mn‐DAP effectively transmits DAP and OVA to the lymph nodes. Experiments showed that this OVA@Mn‐DAP nanoparticle could prevent the growth of B16‐OVA melanoma, and the combination of ICB therapy and OVA@Mn–DAP nanovaccine had more substantial therapeutic effect [92] …”
Section: Combination Of Nanotechnology‐based Immune Checkpoint Blockimentioning
confidence: 98%
“…Experiments showed that this OVA@Mn-DAP nanoparticle could prevent the growth of B16-OVA melanoma, and the combination of ICB therapy and OVA@Mn-DAP nanovaccine had more substantial therapeutic effect. [92] In another study, João reported on the treatment of mannose anti-tumor nano-vaccine in combination with ibrutinib and OX40/PD-1 immune checkpoint. Mannose-based nanovaccine can target dendritic cells, myeloid suppressor ibrutinib can promote CD4 + T cell proliferation and DC maturation, thereby increasing the secretion of related cytokines, and anti-aPD-1 and anti-OX40 antibody had synergistic ICB therapeutic effect.…”
Section: Nano Vaccinementioning
confidence: 99%
“…13,14 The increasing interest in nanotechnology for cancer is due to its unique and attractive features, such as its utility for drug delivery, diagnosis, imaging, and synthetic vaccine development, as well as the inherent therapeutic properties of some nanomaterials. [15][16][17] To precisely control the release of drug at the tumor site and to meet requirements for increased anti-tumor effect and reduced damage to normal tissues, research has made great contributions in the area of stimuli-responsive release of materials (for example, pH, redox state, and enzymes). [18][19][20] Based on the characteristic acidity of the tumor microenvironment, Li et al 21 developed pHresponsive nanoparticles that improved the anti-tumor effect of paclitaxel on drug-resistant and metastatic breast cancer.…”
Section: Introductionmentioning
confidence: 99%